Nanoantibiotics containing membrane-active human cathelicidin LL-37 or synthetic ceragenins attached to the surface of magnetic nanoparticles as novel and innovative therapeutic tools: current status and potential future applications - Urszula Wnorowska; Krzysztof Fiedoruk; Ewelina Piktel; Suhanya V. Prasad; Magdalena Sulik; Marianna Janion; Tamara Daniluk; Paul B. Savage; Robert Bucki (Journal of Nanobiotechnology, 2020)
Abstract Nanotechnology-based therapeutic approaches have attracted attention of scientists, in particular due to the special features of nanomaterials, such as adequate biocompatibility, ability to improve therapeutic efficiency of incorporated drugs and to limit their adverse effects. Among a variety of reported nanomaterials for biomedical applications, metal and metal oxide-based nanoparticles offer unique physicochemical properties allowing their use in combination with conventional antimicrobials and as magnetic field-controlled drug delivery nanocarriers. An ever-growing number of studies demonstrate that by combining magnetic nanoparticles with membrane-active, natural human cathelicidin-derived LL-37 peptide, and its synthetic mimics such as ceragenins, innovative nanoagents might be developed. Between others, they demonstrate high clinical potential as antimicrobial, anti-cancer, immunomodulatory and regenerative agents. Due to continuous research, knowledge on pleiotropic character of natural antibacterial peptides and their mimics is growing, and it is justifying to stay that the therapeutic potential of nanosystems containing membrane active compounds has not been exhausted yet.